The Evolution of Birkat al-Fil (from the Fatimids to the Twentieth Century) - Younes, Nadia Fouad (AUC Knowledge Fountain, 2010)
This thesis will be exploring in depth the urban fabric of the area formerly known as Birkat al-Fil, or Elephant Pond, and its modern day transformation into areas such as Hilmiyya and Hilmiyya al-Jadida. Though the pond was eventually filled in the middle of the nineteenth century, the area will still be discussed in terms of its development within the modern era. I have defined the pre-twentieth century area of Birkat al-Fil by historical landmarks such as Bab al-Khalq to the north, the Mosque of Sultan Hasan to the east, and Sayyida Zaynab to the west. The pond area that will be studied and its transformation was encompassed within the triangular area defined as, in the modern era, the Muhammad â Ali spine, which runs from the north to the southeast corner; the Saliba, the southern boundary; and Shariâ Port Said, the southwest to north boundary.